STORE OPERATIONS TO MAINTAIN CACHE COHERENCE - Nair Ravi; Ohmacht Martin; Evangelinos Constantinos (2016)
In one embodiment, a computer-implemented method includes encountering a store operation during a compile-time of a program, where the store operation is applicable to a memory line. It is determined, by a computer processor, that no cache coherence action is necessary for the store operation. A store-without-coherence-action instruction is generated for the store operation, responsive to determining that no cache coherence action is necessary. The store-without-coherence-action instruction specifies that the store operation is to be performed without a cache coherence action, and cache coherence is maintained upon execution of the store-without-coherence-action instruction.